A Silver Bowl in the Ashmolean Museum - Hamilton, R. W.
Ashmolean 1964.482: “fashioned in Assyria during the seventh century; carried off . . . in 612 B.C.; it was embellished thereafter with heraldic lions . . . at Ecbatana”.